Inheritance - Toynton, Evelyn, 1950- (Other Press, 2019)
"As an American woman enamored of England becomes increasingly close to a dysfunctional aristocratic family, she discovers the land of Keats, Shelley, and Byron isn't as romantic as she had imagined. After the sudden death of her husband, Annie Devereaux flees to England, the site of her absent father's lifelong fantasies. A chance encounter on one of her last nights in London leads Annie to abandon her complicated family back home in America in favor of a shared flat with Julian, a disillusioned bureaucrat and son of an infamous British scientist, Helena Digby. Their romance moves quickly as Annie meets Julian's two sisters, Isabel and Sasha, and becomes infatuated with their idyllic childhood in England's West Country. But the more she unearths, the more irritable Julian becomes. When ghosts from his past finally reveal Julian's violent temper, Annie finds herself alone in London yet again, though this time it is her burgeoning friendship with Isabel that persuades her to stay. With Isabel as her reluctant guide, Annie learns of the dark shadow that Helena's fame, madness, and paranoia cast over their quaint countryside life. The family who once embodied Annie's idealized vision of England is in fact ensnared in controversy and betrayal that is inescapable even in their adult years and which continues to bind them together. In this page-turning family drama, Evelyn Tonyton explores the particular pain caused by those closest to us and the unconditional love that allows us to forgive"--